Monitoramento microbiológico da mastite ovina na região de Bauru - SP - Lucheis, Simone Baldini [UNESP]; Hernandes, Gabriela Spinelli; Troncarelli, Marcella Zampoli (My University, 2010)
Mastitis is an acute or a chronic inflammation of the udder, represented for physical, chemical and bacteriological milk alterations. It is notable that ovine milk represents high economic importance, and it can be used in the production of cheeses and other derivates, contributing for the farmer’s recipe enlargement. However, the mastitis in animals can determine the reduction of milk quantity and quality in infected animals. This may determine lambs’ weight loss and increase animal’s mortality. By the other hand, considering Public Health issues, mastitis can cause milk nutrients losses and promote the microorganisms’ multiplication that may lead to diarrheas and to other zoonosis in humans. This study aimed to evaluate 159 sheep mastitis status in 20 small farms located in Bauru (SP) region. Of the 309 colected samples, in 97 (31.4%) were isolated microorganisms of the genus Staphylococcus sp., which them 27.5% being coagulase negative Staphylococcus and 3.9% coagulase positive Staphylococcus. Of 177 isolates, 97 (54.8%) were represented by the genus Staphylococcus sp., which them 57 (58.8%) from pure culture and 40 (41.2%) in association. Most agents isolated were sensitive to antibiotics used in the test. Thus, we could verify the isolation of infectious microorganisms such as coagulase positive and negative Staphylococcus and, as well in dairy cattle, preventive measures to obtain hygienic milk are extremely important in order to get a final product with quality and safe in food and microbiological point of view.

As mastites são inflamações agudas ou crônicas da glândula mamária, caracterizadas por alterações físicas, químicas e bacteriológicas no leite. O leite ovino tem ocupado uma importância cada vez maior no mercado, podendo ser utilizado na produção de queijo e outros derivados, contribuindo para o aumento da receita do produtor rural. Entretanto, a mastite pode determinar redução, tanto na quantidade quanto na qualidade do leite produzido, levando à redução do ganho de peso dos cordeiros e causando aumento da mortalidade nos animais. Ressalta-se ainda o aspecto de saúde pública, pela redução do nível de nutrientes, assim como a intensa multiplicação microbiana que pode ocasionar diarreias e outras zoonoses. Pretendeu-se com este trabalho avaliar a frequência de casos de mastite em 159 ovelhas procedentes de vinte pequenas propriedades localizadas em Bauru, SP, e região. Das 309 amostras colhidas, em 97 (31,4%) foram isolados micro-organismos do gênero Staphylococcus sp., sendo 27,5% Staphylococcus sp. coagulase negativos e 3,9% Staphylococcus sp. coagulase positivos. Dos 177 isolamentos, 97 (54,8%) foram representados pelo gênero Staphylococcus, sendo 57 (58,8%) obtidos em cultura pura e 40 (41,2%) em associação. A maioria dos agentes isolados foi sensível aos antimicrobianos utilizados no teste. Assim, pôde-se verificar o isolamento de micro-organismos contagiosos, como Staphylococcus sp. coagulase negativo e positivo, sendo que, assim como na bovinocultura leiteira, medidas de profilaxia para obtenção higiênica do leite são de extrema importância para adquirir-se um produto final de qualidade, e seguro do ponto de vista microbiológico e alimentar.
Microbiological monitoring of the region of ovine mastitis Bauru, SP, Brazil
Keywords: Microbiology; Milk; Ovine mastitis; Bauru; Microbiologia; Leite; Mastite ovina; Bauru